2018
DOI: 10.1051/ijmqe/2018003
|View full text |Cite
|
Sign up to set email alerts
|

Control chart applications in healthcare: a literature review

Abstract: The concept of Statistical process control (SPC) was given by the physicist Walter Shewhart in order to improve the industrial manufacturing. The SPC was firstly applied in laboratory and after then shifted to patient level in hospitals. As there is more involvement of human in healthcare, the chances of errors are also more. SPC i.e., control chart can help in determining the source of errors by identifying the special and common causes of variations. This paper presents the review of literature on the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 55 publications
0
43
0
5
Order By: Relevance
“…Kalite ile ilgili çok fazla ilgilenilmemesine rağmen bu sektörde yatırım sürekli büyümektedir. 10 Kontrol çizelgeleri, çalışma çizelgeleri, neden-sonuç şemaları, Pareto çizelgeleri ve süreç akış şemaları bir sağlık kuruluşundaki bakım ve hizmet kalitesini etkileyen yapıları ve süreçleri tanımlamak ve analiz etmek için temel araçlardır. Bunların temel amacı kurumların veriye ve geçerli çıkarımlara dayalı eylemde bulunmasına yardımcı olmaktır.…”
Section: Sağlik Hi̇zmetleri̇nde Kontrol çİzelgeleri̇unclassified
See 2 more Smart Citations
“…Kalite ile ilgili çok fazla ilgilenilmemesine rağmen bu sektörde yatırım sürekli büyümektedir. 10 Kontrol çizelgeleri, çalışma çizelgeleri, neden-sonuç şemaları, Pareto çizelgeleri ve süreç akış şemaları bir sağlık kuruluşundaki bakım ve hizmet kalitesini etkileyen yapıları ve süreçleri tanımlamak ve analiz etmek için temel araçlardır. Bunların temel amacı kurumların veriye ve geçerli çıkarımlara dayalı eylemde bulunmasına yardımcı olmaktır.…”
Section: Sağlik Hi̇zmetleri̇nde Kontrol çİzelgeleri̇unclassified
“…biçiminde sıralanabilir. 10,15 Kalite kontrol çizelgeleri özellikle olumsuz olayların takibinde kullanılmaktadır. Deming tarafından sağlık hizmetlerinde olumsuz olayları izlemek için kontrol çizelgelerinin kullanılması önerilmiştir.…”
Section: Sağlik Hi̇zmetleri̇nde Kontrol çİzelgeleri̇unclassified
See 1 more Smart Citation
“…Maccarthy & Wasusri, [9]; Clemente et al, [10]; Suman et al, [11]; Wiemken, [12]) and are increasingly being adopted for public health surveillance (Woodall,[13]; Morton et al, [14]; Benneyan, [8]). It is suggested that understanding, monitoring and controlling variation in clinical variables is an important part of clinical practice Glasziou et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is not a surprise that the health care sector has seen an increased use of control chart too. Uses within this sector range from quality assurance to administrative data analysis, patient‐level monitoring, and many more . In one example, control charts were used as part of system engineering methods applied to health care delivery .…”
Section: Introductionmentioning
confidence: 99%